Transformation of the municipal waste management sector in Poland. A case study of the Świętokrzyskie Region = Transformacja sektora gospodarki odpadami komunalnymi w Polsce. Studium przypadku województwa świętokrzyskiego - Rybaczewska-Błażejowska, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The article discusses the transformation of the municipal waste management sector in Poland, taking place during 2011-2013, upon the case study of the Świętokrzyskie Region. The pivotal assumptions of the new model of municipal waste management in Poland are: the change of the owner of municipal waste that became communities, the improvement of the municipal waste collection, transportation and processing, and finally regionalization that means the division of the territory of Poland into municipal waste management regions.
Keywords: odpady komunalne; zarządzanie; zrównoważony rozwój; województwo świętokrzyskie; municipal waste; management; sustainability; Świętokrzyskie Region